COMPARISON OF PROJECT-BASED LEARNING AND DISCOVERY LEARNING ON BIOLOGY LEARNING OUTCOMES BY CONTROLLING STUDENTS’ INITIAL KNOWLEDGE - Sirih, Muhammad; Ibrahim, Nurdin; Priyono, Priyono (Didaktika Biologi: Jurnal Penelitian Pendidikan Biologi, 2020)
The study aimed to compare the influence of project-based learning and discovery learning models on biology learning outcomes by controlling students' initial knowledge. The aim of this study was also to analyze the role of initial knowledge in learning by involving the both learning models. The study was conducted in State Senior High School 4 Kendari using quasi-experimental design (Non-equivalent pretest and posttest control-group). The samples were conducted by a random sampling technique, Class XI MIA 1 as the experimental class and Class XI MIA 4 as a control class. The variables consisted of: a) biology learning outcomes as the dependent variable; b) learning models (project-based learning and discovery learning) as the independent variables; and c) students' initial knowledge as the covariate variable. The data were analyzed using ANCOVA at a significance level 0.05. The study results showed there was significant difference of biology learning outcomes between students that taught using the project-based learning and students taught using the discovery learning by controlling the initial knowledge (sig. 0.025 < ? 0.05). The average of students’ biology learning outcomes that taught using the project-based learning (76.63) was higher than students taught using the discovery learning (73,37). Then, there was the influence of the initial knowledge on students’ biology learning outcomes (sig. 0.000 < ? 0.05). The initial knowledge is one of the crucial prerequisites for learning, conceptualized as knowledge of students' relevant and dominant  content with what they learn. Penelitian ini bertujuan membandingkan pengaruh model project-based learning dandiscovery learning terhadap hasil belajar biologi dengan mengontrol pengetahuan awal siswa. Penelitian juga bertujuan menganalisis peran pengetahuan awal dalam pembelajaran. Penelitian dilakukan di SMA Negeri 4 Kendari dengan menggunakan desain eksperimen semu (non-ekuivalen pretest dan posttest control group). Pengambilan sampel dilakukan dengan teknik random sampling, Kelas XI MIA 1 sebagai kelas eksperimen dan Kelas XI MIA 4 sebagai kelas kontrol. Variabel penelitian terdiri dari: a) hasil belajar biologi sebagai variabel terikat; b) model pembelajaran (project-based learning dan discovery learning) sebagai variabel bebas; dan c) pengetahuan awal siswa sebagai variabel kovariat. Analisis data menggunakan ANCOVA pada tingkat signifikansi 0,05. Hasil penelitian menunjukkan terdapat perbedaan yang signifikan hasil belajar biologi antara siswa yang diajar menggunakan project-based learning dan siswa yang diajar menggunakan discovery learning dengan mengontrol pengetahuan awal (sig. 0,025 <? 0,05). Rata-rata hasil belajar biologi siswa yang diajar menggunakan project-based learning (76,63) lebih tinggi daripada siswa yang diajar menggunakan discovery learning (73,37). Kemudian ada pengaruh pengetahuan awal terhadap hasil belajar biologi siswa (sig. 0,000 <? 0,05). Pengetahuan awal merupakan salah satu prasyarat penting untuk pembelajaran, dikonseptualisasikan sebagai pengetahuan tentang konten siswa yang relevan dan dominan dengan apa yang mereka pelajari.